Multiple common and rare variants of ABCG2 cause gout - Higashino, Toshihide; Takada, Tappei; Nakaoka, Hirofumi; Toyoda, Yu; Stiburkova, Blanka; Miyata, Hiroshi; Ikebuchi, Yuki; Nakashima, Hiroshi; Shimizu, Seiko; Kawaguchi, Makoto; Sakiyama, Masayuki; Nakayama, Akiyoshi; et al. (RMD open, 2017)
OBJECTIVE: Previous studies have suggested an association between gout susceptibility and common dysfunctional variants in ATP-binding cassette transporter subfamily G member 2/breast cancer resistance protein (ABCG2/BCRP), including rs72552713 (Q126X) and rs2231142 (Q141K). However, the association of rare ABCG2 variants with gout is unknown. Therefore, we investigated the effects of rare ABCG2 variants on gout susceptibility in this study. METHODS: We sequenced the exons of ABCG2 in 480 patients with gout and 480 healthy controls (Japanese males). We also performed functional analyses of non-synonymous variants of ABCG2 and analysed the correlation between urate transport function and scores from the protein prediction algorithms (Sorting Intolerant from Tolerant (SIFT) and Polymorphism Phenotyping v2 (PolyPhen-2)). Stratified association analyses and multivariate logistic regression analysis were performed to evaluate the effects of rare and common ABCG2 variants on gout susceptibility. RESULTS: We identified 3 common and 19 rare non-synonymous variants of ABCG2. SIFT scores were significantly correlated with the urate transport function, although some ABCG2 variants showed inconsistent scores. When the effects of common variants were removed by stratified association analysis, the rare variants of ABCG2 were associated with a significantly increased risk of gout (OR=3.2, p=6.4×10-3). Multivariate logistic regression analysis revealed that the size effect of these rare ABCG2 variants (OR=2.7, p=3.0×10-3) was similar to that of the common variants, Q126X (OR=3.4, p=3.2×10-6) and Q141K (OR=2.3, p=2.7×10-16). CONCLUSIONS: This study revealed that multiple common and rare variants of ABCG2 are independently associated with gout. These results could support both the 'Common Disease, Common Variant' and 'Common Disease, Multiple Rare Variant' hypotheses for the association between ABCG2 and gout susceptibility.
Keywords: gout; epidemiology; gene polymorphism; arthritis